PEDAGOGICAL CONDITIONS FOR FORMATION OF SPORTS SKILLS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Based on a theoretical analysis of scientific and methodological literature, the essence and content of sports motivation and the features of its connection with the personal qualities of athletes are determined. Pedagogical conditions for the formation of sports motivation of volleyball players aged 13-14 years have been identified.